2001
DOI: 10.1007/s005310100195
|View full text |Cite
|
Sign up to set email alerts
|

Peraluminous granites frequently with mantle-like isotope compositions: the continental-type Murzinka and Dzhabyk batholiths of the eastern Urals

Abstract: Murzinka and Dzhabyk are continental-type batholiths of the middle and southern East Uralian domain. They comprise mainly undeformed peraluminous K-rich granites whose elemental composition is similar to some late-Variscan granites of western Europe, but with much more primitive Sr and Nd isotope ratios. Murzinka (2545 Ma) is composed of silica-rich granites forming two different rock series with a 87 Sr/ 86 Sr init of 0.709 and 0.704, respectively. Both series have enormous variations in eNd 255 (±11.9 to ±0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
1
5

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(31 citation statements)
references
References 23 publications
3
22
1
5
Order By: Relevance
“…The relatively low A/CNK values, Rb/Sr (mostly below unity) and Rb/Ba (< 0.45) as well as high CaO/Na 2 O ratios (0.15-0.84) are typical of magmas generated by partial melting of feldspar-rich psammitic or intermediate meta-igneous sources (Sylvester 1998;Jung and Pfänder 2007). Such a notion is also supported by the major-element plots of Gerdes et al (2002) and Jung and Pfänder (2007) shown in Fig. 14.…”
Section: Age and Character Of The Protolith To The Orthogneissessupporting
confidence: 62%
“…The relatively low A/CNK values, Rb/Sr (mostly below unity) and Rb/Ba (< 0.45) as well as high CaO/Na 2 O ratios (0.15-0.84) are typical of magmas generated by partial melting of feldspar-rich psammitic or intermediate meta-igneous sources (Sylvester 1998;Jung and Pfänder 2007). Such a notion is also supported by the major-element plots of Gerdes et al (2002) and Jung and Pfänder (2007) shown in Fig. 14.…”
Section: Age and Character Of The Protolith To The Orthogneissessupporting
confidence: 62%
“…5). This data shows a good consensus with Gerdes et al (2002), who published isotope data from the Dzhabyk pluton.…”
Section: Mswd -Mean Squared Weighted Deviatessupporting
confidence: 73%
“…However, this model is inconsistent with geochemical and geophysical data. Nd-isotope data from Gerdes et al (2002) document a crustal residence time that is too brief to support the microcontinental concept. The crustal density below the East Uralian Zone is significantly higher than in a typical continental crust (Döring & Götze 1999).…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Despite their modest size ( Fig. 1) almost every pluton comprises a great variety of rocks, a continuum from gabbros or diorites to leucogranites (Fershtater, 1984;Fershtater et al, 1994;Bea et al, 2002;Gerdes et al, 2002). Though this notable geochemical diversity might have resulted from different factors, compelling evidence firmly points to crystal fractionation as the main cause of differentiation (Fershtater, 1987).…”
Section: Introductionmentioning
confidence: 99%